The right to housing and urban inequalities in Brazil: perspectives based on the work of Ermínia Maricato (Revista do Tribunal Regional Federal da 3ª Região, 2026)
This article aims to analyze the right to housing in Brazil, highlighting its relevance to understanding urban inequalities and the limitations of public housing policies. The research is characterized as qualitative, bibliographical, and exploratory in nature, using the deductive method to articulate the fundamentals of Urban Law with the theoretical contributions of Ermínia Maricato. Initially, a brief historical overview of the formation of Brazilian cities is presented, followed by an analysis of the concept and importance of the right to decent housing as a fundamental right. Subsequently, these elements are related to the author's reflections on the national urban reality. It is observed that the Brazilian urbanization process, historically marked by profound structural inequalities, was conducted under the logic of real estate valuation and socio-spatial segregation, to the detriment of the realization of social rights. In this context, in light of Maricato's contributions, it is demonstrated that precarious housing and urban exclusion are direct consequences of exclusionary urban policies and insufficient state action in guaranteeing access to the city. It is concluded that overcoming this scenario demands the implementation of integrated, inclusive, and socially oriented public policies, with the Public Authorities having a responsibility to promote the realization of the right to decent housing as a fundamental instrument for reducing urban inequalities and achieving social justice.
Keywords: right to housing; urban inequality; urban policy; Urban Law; socio-spatial segregation